(untitled) (Research, Society and Development, 2023)
The objective of this article is to identify which practices have been developed by hospital psychologists in the context of child hospitalization. This is a systematic review of the national literature published in the last 10 years (2013-2023) through searches in the databases: Electronic Journals of Psychology (PePSIC), Virtual Health Library (BVS) and Scientific Electronic Library Online (SciELO). These databases were chosen because they present studies in the areas of hospital psychology and health psychology. To this end, a combination of the following descriptors and Boolean operators was applied in the three databases: psychology and hospital and "hospitalized child", since through the combination of these search engines, the results obtained showed greater representation within the intended theme. Three papers were included and another 68 were excluded after analysis. Thus, a low number of studies focused on this topic was found. In this way, it became evident that advances are needed at the scientific level and in the performance of these professionals in Brazilian hospital institutions with a view to scientific dissemination in this area.